MEMBERDAYAKAN PROGRAM STUDI ILMU KOMUNIKASI - Bayquni, Bayquni (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2009)
By  communication   human  can  live  their  life. communication    human  can socialization.   By human  can  make  and  develop  their  culture. But,  by that kind  of communication.   can we do professional,    when Department. of Communication   as cm intermediate  scholar  and  this field  can be accomplish by  another  subject  of science?  Do  curriculum   of  Communication   Department over a barrel or   its own and what is the weakness  of curriculum  that applied  in Communication    Department?    This  paper   tried   to   explain   the   content   of curriculum  indeed by Communication   Department.